2015
DOI: 10.1111/add.12835
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ exposure to tobacco and alcohol content in YouTube music videos

Abstract: AimsTo quantify tobacco and alcohol content, including branding, in popular contemporary YouTube music videos; and measure adolescent exposure to such content.DesignTen‐second interval content analysis of alcohol, tobacco or electronic cigarette imagery in all UK Top 40 YouTube music videos during a 12‐week period in 2013/14; on‐line national survey of adolescent viewing of the 32 most popular high‐content videos.SettingGreat Britain.ParticipantsA total of 2068 adolescents aged 11–18 years who completed an on‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 33 publications
2
68
0
2
Order By: Relevance
“…The most researched social media site in the tobacco control field is YouTube, with many studies describing the prevalence and type of tobacco-related imagery on the site, ranging from product reviews to smoking fetish imagery (Cranwell et al, 2015;Elkin, Thomson, & Wilson, 2010;Forsyth & Malone, 2010;Freeman & Chapman, 2009;Kim, Paek, & Lynn, 2010). An early study analysed the themes and content of the most viewed videos relating to the five leading cigarette brands (Elkin et al, 2010).…”
Section: Tobaccomentioning
confidence: 99%
See 2 more Smart Citations
“…The most researched social media site in the tobacco control field is YouTube, with many studies describing the prevalence and type of tobacco-related imagery on the site, ranging from product reviews to smoking fetish imagery (Cranwell et al, 2015;Elkin, Thomson, & Wilson, 2010;Forsyth & Malone, 2010;Freeman & Chapman, 2009;Kim, Paek, & Lynn, 2010). An early study analysed the themes and content of the most viewed videos relating to the five leading cigarette brands (Elkin et al, 2010).…”
Section: Tobaccomentioning
confidence: 99%
“…Most of these videos contained tobacco brand content (71%) or the brand name in the title (71%). A content analysis of UK Top 40 YouTube music videos showed that tobacco imagery appeared in 22% of the videos, and tobacco branding in 4% (Cranwell et al, 2015). A recent comprehensive analysis of the 70 most popular cigarette brands on YouTube revealed over 120,000 pro-tobacco videos (Liang et al, 2015).…”
Section: Tobaccomentioning
confidence: 99%
See 1 more Smart Citation
“…ABAs are important to assess because they may function as advertising, whether or not they are paid for or sanctioned by the alcohol industry (Primack et al, 2014). Furthermore, developing brand recognition is a crucial step in the marketing of any product, and companies attempt to create positive associations with their brands through product placement activities (Barry, 2016;Cranwell et al, 2015). Moreover, brand recognition and having a favorite brand are independent, potent risk factors for the initiation and maintenance of the use of these substances among adolescents (Henriksen et al, 2008;Volk et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming clear, however, that some music videos contain substantial tobacco and alcohol imagery,9–11 including branding, and that these portrayals are often positive 10…”
Section: Introductionmentioning
confidence: 99%